The screening of the functional microRNA binding site SNPs in sporadic colorectal cancer genes. Issue 6 (3rd June 2017) - He, Hongjuan; Lei, Lei; Chen, Erfei; Xu, Xiaona; Wang, Lili; Pan, Junqiang; Yang, Fangfang; Wang, Min; Dong, Jing; Yang, Jin
ABSTRACT: Sporadic colorectal cancer (sCRC) is one of the most commonly diagnosed cancers worldwide, but few genetic markers have been identified and used for its early detection. MicroRNAs are diverse cellular regulators in cancer pathogenesis that bind to the 3′-untranslated region (3′-UTR) of their target mRNAs, and variants within the miRNA target sites on sCRC-related genes may influence its pathogenesis. To investigate this possibility, we used a bioinformatical method to screen SNPs for putative changes in miRNA recognition sites within the 3′-UTR of sCRC-related genes. The rs11466537 single nucleotide polymorphism was predicted to modify the regulation of hsa-miR-1193 on the Transforming Growth Factor β Receptor II ( TGFBR2 ) gene. Additionally, luciferase reporter assays indicated that hsa-miR-1193 bound the T allele more strongly than the A allele of rs11466537 (with A being the less frequent variant), and real time-polymerase chain reaction and western blot analysis showed that TGFBR2 is significantly repressed by hsa-miR-1193. Furthermore, overexpression of hsa-miR-1193 promoted HT-29 cell proliferation, while the loss of hsa-miR-1193 inhibited the process. Finally, the rs11466537 genotyping result revealed that the frequency of A allele carriers was 1.5% in the control blood samples, but 0 in the sCRC patients' normal colon tissue samples. Our results demonstrated that hsa-miR-1193 may be involved in sCRC tumourigenesis at least in part by suppression of TGFBR2, and the A allele of rs11466537 disturbed the regulation of hsa-miR-1193 on TGFBR2.